2020
DOI: 10.22460/project.v3i6.p805-815
|View full text |Cite
|
Sign up to set email alerts
|

L2 Writing Strategies Used by High School Students

Abstract: Writing is a challenging activity that comprises a complex cognitive process, as well as various strategies. Furthermore, minimal research has been performed on using writing strategies among High School students in the EFL context, specifically in Indonesia. Although the applications of effective strategies have been evidenced to be helpful, many students are not aware of using them to alleviate their writing quality. Therefore, this study aims at investigating English L2 strategies when writing recount texts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…First, the teacher may neglect to teach their students applicable writing strategies (Suriyanti & Yaacob, 2016). Sometimes students do not realize that writing activities are recursive and non-linear, so the teachers need to introduce them to the various writing strategies required (Arifin, 2020). To overcome this obstacle, teacher capacity building training is needed.…”
Section: Discussionmentioning
confidence: 99%
“…First, the teacher may neglect to teach their students applicable writing strategies (Suriyanti & Yaacob, 2016). Sometimes students do not realize that writing activities are recursive and non-linear, so the teachers need to introduce them to the various writing strategies required (Arifin, 2020). To overcome this obstacle, teacher capacity building training is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers must concentrate on using various strategies that could not only pique their interest in learning to write but also consider their proficiency levels, areas of interest, and goals when developing instruction to support the learning process in a writing classroom. Think Aloud Protocols (TAPs) (Arifin, 2020), free writing (Alharthi, 2021), and collaborative writing (Calzada & Mayo, 2021) as a strategy to improve learning, educators have to think about including visual representation. According to Buckley and Nerantzi (2020), Visuals may be used in educational contexts when they are intended to educate students on how to organize, generate, and/or finish activities.…”
Section: Using Infographics In Writing Classesmentioning
confidence: 99%
“…This opportunity is given to them by offering them appropriate writing techniques. Earlier research has shown that writing skills and writing strategies are interdependent (Arifin, 2020). Second language learners should therefore be well conversant and equipped with second language writing techniques (Ketabi &Tavokoli, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%